Pengaruh Beban Kerja terhadap Kinerja Guru BK dalam Pengentasan Masalah Belajar Siswa SMA Negeri di Kabupaten Manggarai Timur - Madu, Krispinus; Indrawan, Putu Agus; Apriliana, I Putu Agus (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This study aims to determine the description of the workload of counseling teachers, the description of the performance of counseling teachers in alleviating student learning problems, and the effect of workload on the performance of counseling teachers in alleviating the learning problems of public high school students in East Manggarai Regency. This study used a quantitative approach with a causal comparative design. Data collection techniques used questionnaires on workload and performance of counseling teachers in alleviating student learning problems, with a combination of closed and open questions. This research was conducted in 16 public high schools in East Manggarai Regency with 20 counseling teachers as respondents. The data analysis techniques used were descriptive analysis, analysis requirements test and hypothesis testing with the help of SPSS version 25. The results showed that (1) The workload of counseling teachers in public high schools in East Manggarai Regency is dominant in the high category. (2) The performance of counseling teachers in alleviating learning problems of public high school students in East Manggarai Regency is dominant in the medium category. (3) There is a strong and negative influence between workload on the performance of counseling teachers in alleviating learning problems of public high school students in East Manggarai Regency. This can be seen from the significance value of 0.000 <0.05, the value of (a)= 38.674, the value of (b)= -1.198, and the value of R square of 70.8%. Based on the results of the study, it is concluded that the workload of counseling teachers has a strong and negative effect on the performance of counseling teachers in alleviating learning problems of public high school students in East Manggarai Regency.